BURDEN RATES–MACHINE HOURS VERSUS DIRECT LABOR HOURS. - Patrick, A. W. (The Accounting Review, 1961)
Abstract In selecting a measure of activity to be used in applying manufacturing burden to product, a typical cost accounting text includes a few brief remarks about direct labor hours, direct labor cost, machine hours, and units of product. The fact that machinery is the main factor in production does not necessarily mean that machine hours is a measure of activity which provides more accurate costing than does direct labor hours. Cost accounting texts, in their discussion of machine hours versus direct labor hours, frequently seem to avoid the real issues. Very often, unless the instructor amplifies the textbook statements considerably, it is likely that the student will not get a satisfactory answer to the basic question. One of the issues which has not received its fair share of attention is the general superiority for product costing purposes of rates established by machine cost centers which include only homogeneous equipment over a single rate established for a department which includes heterogeneous equipment. It has been argued that machine hours is a better basis than direct labor hours under the following conditions, the process is a relatively continuous one; and cost responsibility centers include heterogeneous equipment and burden rates are established by cost responsibility centers.